Comparison of physical fitness and anthropometrical profiles among brazilian female soccer national teams from u15 to senior categories - Ramos, G. P.; Nakamura, F. Y.; Penna, E. M.; Mendes, T. T.; Mahseredjian, F.; Lima, A. M.; Garcia, E. S.; Prado, L.; Coimbra, C. C. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to compare anthropometric and physical fitness of Brazilian female national team soccer players from the U15 to senior categories, and to compare the physical performance between selected and nonselected players. Subjects included 231 athletes (U15, n = 46, U17, n = 49, U20, n = 98, and Senior, n = 38). Body mass, height, sum of skinfolds, squat jump (SJ), countermovement jump (CMJ), 20-m linear sprint, and Yo-Yo IR1 were assessed. The U15 players were shorter than all other groups (p < 0.01) and lighter than U20 players (p < 0.01). Regarding physical tests, Senior athletes presented higher SJ compared with U20, and both showed higher CMJ and SJ compared with the U15 and U17 (p < 0.05). Senior athletes were also faster than players of all other categories in 20-m sprint (p < 0.01) and covered the greatest distance in the Yo-Yo IR1 (p < 0.05). U20 were better in the Yo-Yo IR1 than the younger groups (p < 0.05). When comparing selected and nonselected players, no differences were identified in anthropometric measures (p > 0.05). However, selected players from U17, U20, and Senior teams showed better performance in Yo-Yo IR1 than nonselected ones (p < 0.05). Finally, selected senior athletes also presented higher CMJ and SJ than nonselected players (p < 0.05). These results suggest that, although there is a tendency for maintenance in anthropometric measures from the age of 15 years, there are substantial improvements in speed, lower-body power, and aerobic capacity from U20 age group. In addition, it seems that intermittent aerobic fitness contributes to the selection of players to international tournaments in national teams.